PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK POLYTRON DI SHOWROOM POLYTRON SMARTPHONE CITRALAND MALL SEMARANG - Ika Pratiwi, 14.05.51.0023; Wuryan, Sophiyanto (Students' Journal of Economic and Management, 2018)
The purpose of this study is to analyze the effect of product quality, price, and promotion on purchasing decisions. The population and sample of this research is the buyer of Polytron Smartphone brand in Polytron Smartphone Showroom Citraland Mall Semarang. Sampling method used in this research is Purposive Sampling method with the number of samples of 100 respondents. Data collected questionnaires analyzed by using Factor Analysis to test the validity of question items, alpha croanbach formula to test the reliability of the instrument, regression analysis to test the magnitude of partial influence of each independent variable tested with the coefficient of determination. The results showed that there is a positive and significant influence between product quality, price, promotion of purchasing decisions Smartphone brand Polytron.Keywords : Product Quality, Price, Promotion, and Purchase decision.